INVENTARISASI JAMUR MAKROSKOPIS DI KAWASAN PENYANGGA (BUFFER ZONE) PERKEBUNAN KELAPA SAWIT KILIRAN JAO KECAMATAN KAMANG BARU KABUPATEN SIJUNJUNG - Tyaningsih, Sulis - (STKIP PGRI Sumbar, 2014)
Fungi is life organism that have not chlorophyll, same with plant because have wall cell and non â motile. This research is to know macroscopic fungi species where is founded at Buffer Zone Plantation Garden Kiliran Jao Kecamatan Kamang Baru Kabupaten Sijunjung. Physic and chemical factors: air temperature, air dampness, ground pH in Buffer Zone. The research is about Inventarization of Macroscopic Fungi in Buffer Zone Plantation Garden Kiliran Jao Kecamatan Kamang Baru Kabupaten Sijunjung have done in June â August 2014. Method that is used in this research which is observation and direct collection toward macroscopic fungi. Identification is done in Botanical Laboratory (Biology) STKIP PGRI Sumatera Barat which can be got 25 species from macroscopic fungi where is invite to 3 Classis, 5 Ordo, 8 Familia, 14 Genus. In addition, physic and chemical factor: air temperature of 26.4 - 29,70C, air dampness of 71 - 84%, ground pH 6.6 - 6.8.